2005
DOI: 10.1128/jb.187.9.3206-3213.2005
|View full text |Cite
|
Sign up to set email alerts
|

Autoinduction in Erwinia amylovora : Evidence of an Acyl-Homoserine Lactone Signal in the Fire Blight Pathogen

Abstract: Erwinia amylovora causes fire blight disease of apple, pear, and other members of the Rosaceae. Here we present the first evidence for autoinduction in E. amylovora and a role for an N-acyl-homoserine lactone (AHL)-type signal. Two major plant virulence traits, production of extracellular polysaccharides (amylovoran and levan) and tolerance to free oxygen radicals, were controlled in a bacterial-cell-density-dependent manner. Two standard autoinducer biosensors, Agrobacterium tumefaciens NTL4 and Vibrio harvey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 51 publications
2
53
1
1
Order By: Relevance
“…Many transgenic plant species expressing AiiA have been shown to be more resistant to soft rot disease (85,91,92); however, the use of such plants in food production has been met with strong resistance from consumers, propelling the development of alternative quorum-quenching approaches. Bacterially mediated quorum quenching using AiiA was also demonstrated to be beneficial against plant pathogens, both when aiiA was expressed in the pathogenic bacterium itself and during coinoculation of the pathogen with bacteria naturally producing AiiA or engineered bacterial strains expressing heterologous AiiA (88,89,(93)(94)(95)(96). AiiA was also shown to have potential for use in aquaculture, as carp fed either recombinant AiiA protein or Bacillus expressing aiiA were more resistant to infection by the fish pathogen Aeromonas hyrophila (361,362).…”
Section: Qsi Success Storiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many transgenic plant species expressing AiiA have been shown to be more resistant to soft rot disease (85,91,92); however, the use of such plants in food production has been met with strong resistance from consumers, propelling the development of alternative quorum-quenching approaches. Bacterially mediated quorum quenching using AiiA was also demonstrated to be beneficial against plant pathogens, both when aiiA was expressed in the pathogenic bacterium itself and during coinoculation of the pathogen with bacteria naturally producing AiiA or engineered bacterial strains expressing heterologous AiiA (88,89,(93)(94)(95)(96). AiiA was also shown to have potential for use in aquaculture, as carp fed either recombinant AiiA protein or Bacillus expressing aiiA were more resistant to infection by the fish pathogen Aeromonas hyrophila (361,362).…”
Section: Qsi Success Storiesmentioning
confidence: 99%
“…Following these initial reports, aiiA genes were identified in various other Bacillus species (56,60,(87)(88)(89), and heterologous expression of various aiiA alleles in numerous pathogenic bacteria, including P. aeruginosa and Burkholderia thailandensis, reduced AHL accumulation and altered QS-dependent behaviors (60,90). Additional studies have since provided further evidence of the utility of enzymatic quorum quenching for disease prevention and treatment in a variety of plant models using both transgenic plant species (91,92) and wild-type (WT) and engineered AiiA-expressing bacteria (88,89,(93)(94)(95)(96). Importantly, the level of aiiA expression appears to be a crucial determinant in the efficiency of AHL degradation and subsequent success in disease prevention.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…The expression of aiiA in transformed E. carotovora significantly attenuates pathogenicity in some crops (6). Expression of aiiA in E. amylovora impairs EPS production and reduces virulence on apple leaves (18). Transgenic plants expressing AHL lactonase exhibited significantly enhanced resistance to E. carotovora infection (5).…”
mentioning
confidence: 99%
“…Pantoea stewartii regulates exopolysaccharide (EPS) biosynthesis and pathogenicity in sweet corn by AHLs (28). Erwinia amylovora produces one AHL and regulates EPS biosynthesis, tolerance to hydrogen peroxide, and the development of symptoms on apple leaves (18). Agrobacterium vitis causes necrosis on grape plants and a hypersensitive-like response on tobacco plants by a quorumsensing system (30).…”
mentioning
confidence: 99%
“…Given that a number of plant and animal bacterial pathogens (such as several Erwinia species, Pseudomonas aeruginosa and Xenorhabdus nematophilus) show AHL-dependent production of virulence factors, it has been suggested that the QS system could be used as a target for therapeutic approaches (4) also using quorum quenching enzymes. Although such approaches to control human and animal pathogens still need to be carefully investigated (5), the use of heterologous expression of bacterial AHL-lactonases in plants for protection against such infections as the blight disease shows considerable promise (6).…”
mentioning
confidence: 99%